Partnership is important and we should stick with it. - GREENIDGE, Carl (1997)
Explains that the ACP group contains countries which combine three distinct characteristics: (1) it has a large proportion of the world's least developed countries; (2) most of them are trade dependent; and, (3) the majority rely on the European Union market. These characteristics provide a strong argument for continuing special treatment, and ACPs will argue for continuing trade preferences at the end of the current Lome Convention.